SYNTHESIS OF 4-AMINO-BENZO[F]ISOINDOLE DERIVATIVES BY REACTION 1-AMINO-2-ARYLISOINDOLES WITH MALEIMIDES: УДК 547.759.4 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2013)
Investigated the reactivity of 1-amino-2-arylisoindoles, the main tautomeric forms for which is imine form. It is shown that the reaction of 1-amino-2-arylisoindoles with maleimides produces derivatives of 4-amino-benzo[f]isoindole. Developed two new methods for the synthesis of fluorescent derivatives of 4-amino-benzo[f]isoindole, which have several advantages relative described earlier in the literature: reaction speed, simple selection of products with high purity, better outputs.
Keywords: isoindole, rearrangement, bis-Michael adduct